Donor‐derived duodenal adenocarcinoma of a bladder‐drained pancreas allograft. Issue 9 (2nd April 2022) - Isaacson, Dylan; Steggerda, Justin; Xue, Yue; Wren, James; Javeed Ansari, Mohammed; Auffenberg, Gregory B.; Katariya, Nitin
Abstract : The subset of the population that received bladder‐drained allograft pancreata during peak utilization of the technique in the 1990s is approaching 20–30 postoperative years. This time frame is salient, as it parallels the time in which patients in the urologic literature develop adenocarcinomas after bladder reconstruction using gastrointestinal segments. We present the case of a 57‐year‐old simultaneous pancreas/kidney recipient who presented with microhematuria twenty‐four years after transplantation and was found to have an adenocarcinoma of the duodenum of his failed, bladder‐drained pancreas. After allograft pancreatectomy/duodenectomy, he remains disease‐free eleven months postoperatively. As this patient population ages, practitioners should consider pathology of the donor duodenum and pancreas in recipients who present with gross or microscopic hematuria. Abstract : This case report present a unique case of donor‐derived duodenal adenocarcinoma of a pancreatic allograft and its implications.